2010
DOI: 10.1007/s10899-010-9216-y
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Guilt and Shame After Gambling Loss

Abstract: In this study we examined the relations between guilt and shame and coping strategies in response to gambling loss. Based on H.B. Lewis's (Shame & guilt in neurosis. New York: International Universities Press, 1971) account of guilt and shame, we proposed that unlike guilt, the experience of shame involves the attribution of gambling loss to stable and global internal factors (i.e., self-devaluation). We hypothesized that problem gambling severity would be more strongly associated with the intensity of shame t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
3
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 22 publications
4
45
3
4
Order By: Relevance
“…For example, a recent study (Yi & Kanetkar, 2011) showed that following gambling losses, problem gamblers experienced more intense shame than low-risk gamblers, whereas the intensity of guilt following gambling losses did not differ. Future research should investigate the possibility that an acute experience of shame may trigger the desire to gamble in problem gamblers.…”
Section: The Shame Versus Guilt Distinctionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a recent study (Yi & Kanetkar, 2011) showed that following gambling losses, problem gamblers experienced more intense shame than low-risk gamblers, whereas the intensity of guilt following gambling losses did not differ. Future research should investigate the possibility that an acute experience of shame may trigger the desire to gamble in problem gamblers.…”
Section: The Shame Versus Guilt Distinctionmentioning
confidence: 99%
“…Even though the construct of coping (Lazarus & Folkman, 1984) has been applied extensively to the study of gambling, few researchers have investigated how individuals cope with gambling losses. Two studies that are notable exceptions (Shepherd & Dickerson, 2001;Yi & Kanetkar, 2011) are briefly summarized below. Shepherd and Dickerson (2001) tested the hypothesis that impaired control over gambling would be positively associated with the use of avoidant coping strategies (e.g., mental disengagement, behavioral disengagement, denial, wishful thinking) in response to specific gambling loss episodes.…”
Section: Shame-versus Guilt-proneness and Coping With Gambling Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited ability to seek help represents a coping strategy associated with shame, and which usually coincides with guilt and resentment towards the original family members (Yi and Kanetkar 2011). This strategy often facilitates the development of PG and results in suicide attempts and/or bankruptcy.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that two feelings were different. Yi and Kanetkar (2011), Lozınskı (2011), Jun and Yeo (2012 researched the relationship between guilt, shame, anger, and fear that are felt as a result of gambling loss, dieting and buying cell phones and coping strategies. According to the results, it was found out that the intensity and severity of gambling were more related to shame while the consumers who felt ashamed because of gambling loss and dieting chose the disengagement strategy among the coping strategies.…”
Section: Coping With Strategiesmentioning
confidence: 99%